A 59-year-old man with Riedel's Thyroiditis, Initial Suspicion of Thyroid Cancer and Improved with Tamoxifen and Corticosteroid Therapy - Ika Hudayani; Himawan Sanusi (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2024)
Riedel's thyroiditis is a rare fibrotic condition involving damage to the thyroid gland and infiltration of surrounding structures. Synonyms of Riedel's thyroiditis include Riedel's goiter, fibrous goiter, ligneous goiter, or chronic invasive fibrous thyroiditis. The inflammatory thyroid condition of Riedel's thyroiditis is a local manifestation of a systemic fibrous or autoimmune process and chronic sclerosis or productive thyroiditis. A 59-year-old man came to the Endocrinology Clinic at Wahidin Sudirohusodo Hospital and was consulted by an oncology surgeon colleague with complaints of a lump in his neck for 2 years before coming to the hospital. Initially the lump was the size of a marble then it got bigger, felt hard, and not painful. The patient had a history of biopsies by surgical colleagues 2 times, the first in May 2022 Fine Needle Aspiration Biopsy with Malignancy (Papillary) results at Bhayangkara Hospital, then the patient was referred to a surgical oncology colleague at Wahidin Sudirohusodo Hospital and a 1-month incision biopsy was performed before going to the endocrine polyclinic with the results of Riedel's Thyroiditis. The patient was then given therapy with Tamoxifen 20 mg per 24 hours orally, and Methylprednisolone 16 mg per 8 hours orally with tapering doses every 7 days. In the treatment during control there were no complaints but complaints of a lump in the neck tended to shrink so the treatment was continued for 2 months then the patient returned to control with a clinical lump in the neck shrinking (Improvement). Riedel's thyroiditis is a disease characterized by an overgrowth of connective tissue that can invade surrounding structures. This connective tissue growth may extend into the recurrent laryngeal nerve. This thyroid inflammatory condition is suspected as a local manifestation of a systemic fibrotic process or an autoimmune process. Commonly used therapies such as glucocorticoids and immunosuppressant agents such as tamoxifen. Steroid treatment is usually given at a dose of 100 mg of prednisolone daily.